2003
DOI: 10.1080/0269249x.2003.9705589
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature and Mixed Species Composition on Diatom Motility and Adhesion

Abstract: Four species of biraphid pennate diatoms (Craticula cuspidata (Kiitzing) D.G. Mann, Stauroneis phoenicenteron (Nitzsch) Ehrenberg, Nitzschia linearis (Agardh) W. Smith, and Pinnularia viridis (Nitzsch) Ehrenberg) were studied to determine the effect of temperature changes on their motility and adhesion to the substratum. The pattern of cell movement in response to temperature was similar in all species; the average cell speed increased with temperature, with a maximal speed at 30-35°C. Temperatures > 35OC caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 43 publications
1
22
0
1
Order By: Relevance
“…Generally, higher but not extreme temperatures increase the motility of unicellular organisms (Maeda et al 1976;Burchard and Marchant 1983). In the study presented here, both species showed greater movement at warmer temperatures, which is consistent with results reported by Cohn et al (2003). By contrast, chilling at 2°C can markedly reduce the migration rhythm of diatoms (Round and Palmer 1966).…”
Section: Effects Of Light and Temperaturesupporting
confidence: 94%
“…Generally, higher but not extreme temperatures increase the motility of unicellular organisms (Maeda et al 1976;Burchard and Marchant 1983). In the study presented here, both species showed greater movement at warmer temperatures, which is consistent with results reported by Cohn et al (2003). By contrast, chilling at 2°C can markedly reduce the migration rhythm of diatoms (Round and Palmer 1966).…”
Section: Effects Of Light and Temperaturesupporting
confidence: 94%
“…In contrast, S. phoenicenteron cells are more likely to stay at a lower position in algal communities, where (because of light irradiance and prior absorbance by other algae) they are more likely to encounter less blue light and more low-level red light. Due to its relatively low light sensitivity as well as its strong adhesion and circular path of motility (Edgar & Pickett-Heaps 1984, Cohn & Weitzell 1996, Cohn et al 2003, P. viridis, is likely to be less sensitive to light cues for its placement within the algal assemblage, less able to actively move longer distances, and more sensitive to the abundance and types of available substrata upon which it can move.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, attached diatoms glide on colonized surfaces. Although diatom motility is a rather complex process [13], a general consensus exists about a mechanism involving adhesive proteins and secretion of EPS, with possible modification of the surrounding environment by mucilage [57]. Hence, the combination of diatom motility with production of adhesive biopolymers can induce degradation M a n u s c r i p t of the fine sized topography of the SH coating.…”
Section: Samples With Superhydrophobic Coatingmentioning
confidence: 99%